The effects of teaching critical thinking skills on EFL high school students’ reading comprehension - Wale, Bantalem Derseh (Ethiopian Journal of Language, Culture and Communication, 2024)
This study investigated the effects of teaching critical thinking skills on EFL high school students’ reading comprehension. To this end, a quasi-experimental pretest-posttest design was used. The data were obtained using test, reflective journal, and interview from two sections of 98 grade ninth Ethiopian students who were selected through random sampling. The experimental group students received critical thinking skills instruction, but the control group students learned through the conventional teaching reading method. Quantitative data were analyzed through independent sample T-test and descriptive statistics, while the qualitative were analyzed through thematic analysis. The findings revealed that there was a statistically significant difference between the experimental and control groups in their reading comprehension. The students who participated in critical thinking skills instruction enhanced their reading comprehension when students in controlled group achieved inadequate reading comprehension. Students who were taught reading skills through critical thinking skills, were able to understand explicit and implicit meanings of reading texts, recognize major themes, examine relationships and differences of arguments, and propose alternative explanations. It is, therefore, recommended that researchers, teachers, and students pay due attention to critical thinking skills instruction.